Navigating data science : unleashing the creative potential of artificial intelligence - Singla, Babita; Shalender, Kumar; Singh, Nripendra (Advances in digital technology and data-driven business practices, 2025)
The rapid rise of generative intelligence is apparent from its adoption prospects across industrial sectors. Business leaders are prioritizing applications of Generative Intelligence although the challenges related to this technology adoption also need to be addressed in detail. Navigating Data Science: Unleashing the Creative Potential of Artificial Intelligence can offer significant contributions in the field of generative intelligence in the context of data science and help stakeholders formulate strategies to tackle its adoption, implementation, and control challenges. The research presented here delves into the combined capability of DS and AI with specific reference to real-world business scenarios. From analysing the use of New Age innovations in marketing to science and Technology and the Healthcare sector, the authors contributed to enhance the body of knowledge in the field of DS and AI. The ethical considerations of using AI tools in education, academic research, and Gig workers have also been dealt with in detail in the book. The impact of technology in moulding the overall well-being of employees within the specific framework of their work-life has been discussed by the authors as a key issue to be considered by organizations today. Advances in Digital Technology and Data-Driven Business Practices examines the possibilities, challenges and ethics of a range of technologies applied in business, including: Metaverse, Marketing Automation, Search Engine Optimization (SEO), Search Engine Marketing (SEM), Social Media Marketing, Content Marketing, Analytics and Data Analysis, Augmented Reality (AR) and Virtual Reality (VR), Chatbots and Artificial Intelligence (AI). Adopting and adapting to these technologies is essential for staying competitive and effectively reaching target audiences.